Suitability of Four Anti-arthritic Plants of Sindh Pakistan in Terms of Major and Trace Toxic Metals Profile: Short Communication: Anti-arthritic Plants of Sindh, Pakistan (Biological Sciences - PJSIR, 2022)
Metals profiling of medicinal plants is obligatory to uncover the therapeutic use and safe dose judgment. Therefore, anti-arthritic plant Moringa oleifera (MO), Smilax china (SC), Vernonia anthelmintica (VA) and Colchicum aitchisonii (CA) were screened for heavy metals by Atomic Absorption Spectrophotometer. The study revealed Ca, Na, K and Mg as predominant metals. Pb was not detected  in any plant and their extracts whereas, Fe, Zn, Co, Cr, Cd and Ni accumulated beyond the accepted limits set for medicinal plants according to WHO. Except Cr in Colchicum aitchisonii, toxic metals such as Ni (4.24-8.99), Cd (2.39-4.73) and Cr (3.52-19.39) mg/Kg were found higher in all powder samples with maximum in the Vernonia anthelmintica. All methanolic and aqueous extracts contained Cd and Cr, whereas only one out of four aqueous extracts contanied Ni. It is concluded from the result that these medicinal plants could be a significant source of major nutrients but their inappropriate use may cause noxious effects due to the accumulation of toxic metals. So, constant checking of medicinal plants is needed.